A comparison of reading aloud, silent reading and follower reading. Which is best for comprehension? / Una comparación de lectura en voz alta, lectura en silencio y lectura de seguimiento. ¿Cuál es mejor para la comprensión?. Issue 1 (2nd January 2018) - García-Rodicio, Héctor; Melero, María-Ángeles; Izquierdo, María-Belén
Abstract: When reading in the classroom, teachers may use different methods. We examined the impact of different reading conditions on comprehension. Reading aloud involved reading the text aloud for an audience. Silent reading required the students to read the text silently. Follower reading involved listening to another student read the text aloud while having the text available for individual reading. Thirty-six fifth- and sixth-grade students read texts under the three conditions and then took comprehension tests. The students performed equally well under reading aloud and silent reading. Follower reading resulted in worse comprehension. The data suggest that the follower readers focused on their individual reading, making an effort not to listen to the student reading out loud, which consumed cognitive resources. Since reading aloud in the classroom involves not only one loud reader but also a lot of follower readers, silent reading might be the smartest choice.